Penyuluhan Ekonomi Syariah Bagi Ibu-Ibu PKK Ngeni Waru Sidoarjo (Mengenal Bank Syariah) - Abdul Wahab (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Islamic economics is a branch of science that seeks to view, analyze, and finally solve economic problems in Islamic ways, namely based on Islamic religious teachings, namely the Qur'an and the Sunnah of the Prophet (P3EI, 2012:17). Islamic economics has two main things which are the legal basis of the Islamic economic system, namely the Qur'an and the Sunnah of the Prophet, the laws taken from these two main foundations are conceptually and in principle fixed (cannot change anytime and anywhere)